Assessment of Instructional Facilities in Implementing the Contents of the Motor Vehicle Mechanics’ Work Curriculum in Technical Colleges in North Central Nigeria - Ogbuanya, Therasa Chinyere; David, Usman Auta (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
The training of motor vehicle mechanics is not only expertise demanding, but also requires a lot of facilities which has to be effectively utilized for the realization of instructional objectives. The objectives of the study were (1) to ascertain the availability of instructional facilities; and (2) to find out the extent of the usage of the instructional facilities in implementing the contents of the MVMWC. The population of the study was 465; consisting of 418 male and 38 female MVMW National Technical Certificate (NTC) III graduating students for the 2017/2018 session, in the 22 accredited technical colleges in the North-Central States of Nigeria, and 9 MVMW graduates of technical colleges in the area of study who were operating functional workshops. The study adopted a Multi-stage Sampling Technique to select a sample size of 189 which comprised 165 male and 15 female MVMW NTC III graduating students and 9 MVMW graduates of technical colleges from the area of the study. A questionnaire and Focus Group Discussion (FGD) were used as instruments for data collection. The research questions were analyzed using mean, frequency count, and percentages. The findings of this study revealed: lack of basic instructional facilities for effective implementation of the MVMWC in technical colleges in the North Central States of Nigeria; and a low extent of utilization of the very few instructional facilities available.